The Templars, the Witch, and the Wild Irish : Vengeance and Heresy in Medieval Ireland - Callan, Maeve Brigid, 1970- (Book collections on Project MUSE., 2015)
"Early medieval Ireland is remembered as the "Land of Saints and Scholars, " due to the distinctive devotion to Christian faith and learning that permeated its culture. As early as the seventh century, however, questions were raised about Irish orthodoxy, primarily concerning Easter observances. Yet heresy trials did not occur in Ireland until significantly later, long after allegations of Irish apostasy from Christianity had sanctioned the English invasion of Ireland. In The Templars, the Witch, and the Wild Irish, Maeve Brigid Callan analyzes Ireland's medieval heresy trials, which all occurred in the volatile fourteenth century. These include the celebrated case of Alice Kyteler and her associates, prosecuted by Richard de Ledrede, bishop of Ossory, in 1324. This trial marks the dawn of the "devil-worshipping witch" in European prosecutions, with Ireland an unexpected birthplace"--